Compensation for damage caused by an acute source of danger – as a separate type of delict (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
One of the socio-economic problems in Uzbekistan is traffic accidents, which is the most striking example of the negative consequences of the source of increased risk. At the same time, the study and analysis of the prosessual characteristics of the consideration of cases on compensation for damage caused by a loving source of risk is of great theoretical and practical importance, since it makes it possible to correctly apply the norms of material and prosessual law when considering cases in this cateogria and serves to improve the quality The article covers the same issues.